JENIS-JENIS UDANG DI KAWASAN ESTUARIA DESA BATANJUNG SEBAGAI MODUL PENDAMPING MATERI BIOLOGI SMA KELAS X - Johanto Johanto (Master Program of Biology Education, Universitas Lambung Mangkurat, 2019)
The species of shrimps in the estuarine areain Batanjung Village have great potential for the academic field, and have not been used as a supplementary module for Biologyon animalia concept, phylum Artrophoda in crustaceas class, for the tenth grade ofsenior high school. This research aims to produce avalid module for Biology on the shrimp species in the estuarine region of Batanjung Village for the tenth grade of SMAN 1 Basarang. Theresearch type used is Research and development (R & D). There are 9 steps in this activity.The result of the field research shows that there are 11 species of shrimps, namely Harpiosquilla raphideae. Peneaus monodon, Peneaus merguensis, Peneaus indicus, Peneaus Vanamae, Metapeneaus monoceros, Palaemon adpersus, Palaemon concinnus, Macrobrachium nipponse, Macrobrachium equidens, Macrobrachium rosenbergii. Furthermore, the species of shrimp were designed to be a supplementary module for Biology for the tenth grade of SMA. The teaching materialswere validated by three experts, and the legibility test were done by the tenth-grade students of SMAN-1 Basarang. The results of validity and legibility test shows that the created teaching materials can be used as the supplementary materials for Biology of the tenth grade of SMA.